2016
DOI: 10.1021/acs.jpcb.6b04506
|View full text |Cite
|
Sign up to set email alerts
|

Cation-Induced Hydration Effects Cause Lower Critical Solution Temperature Behavior in Protein Solutions

Abstract: The phase behavior of protein solutions is important for numerous phenomena in biology and soft matter. We report a lower critical solution temperature (LCST) phase behavior of aqueous solutions of a globular protein induced by multivalent metal ions around physiological temperatures. The LCST behavior manifests itself via a liquid-liquid phase separation of the protein-salt solution upon heating. Isothermal titration calorimetry and zeta-potential measurements indicate that here cation-protein binding is an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
97
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(106 citation statements)
references
References 37 publications
6
97
3
Order By: Relevance
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules. This approach enabled us to include all ions explicitly in a two-body system, which is more difficult and computationally costly to realize with coarsegrained models at high ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This work, at a microscopic level, echoes experimental results showing the existence of reentrant condensation in HSA solutions in the presence of trivalent ions [18][19][20] and is also in agreement with recent calorimetry experiments. 45 Different models were used: an atomic model, a coarse-grained model, and a colloidal The colloidal model was used to study the interactions of two spherical colloids representing HSA-like molecules. This approach enabled us to include all ions explicitly in a two-body system, which is more difficult and computationally costly to realize with coarsegrained models at high ion concentrations.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work 45 calorimetry measurements showed that the binding of trivalent ions to the protein surface, and the resulting protein-protein attraction are entropically driven.…”
Section: Addition Of Yclmentioning
confidence: 99%
“…The LLPS binodal has been determined for BSA with YCl 3 , which leads to a lower critical solution temperature (LCST) phase behavior. 43 Here we use USAXS and VSANS to study the kinetics of LCST-LLPS in the dense phases of the BSA-YCl 3 system. First we aim to establish a new method for studying the kinetics of the phase transition based on the advantages of USAXS and VSANS.…”
Section: Introductionmentioning
confidence: 99%
“…[19] Importantly, the driving force for this binding is not enthalpy alone, but hydration entropy. In particular, a physicochemical characterisation of the binding reveals a lower critical solution temperature, [187] and the water coordination around Y 3 + is reduced upon binding to the protein, [188] both of which evidence the release of hydration water molecules with substantial related entropy gains. Finally, we refer the interested reader to a recent overview on the roles of lanthanides in biochemistry by Daumann.…”
Section: Local Picture Of Cation Binding Sites Of Proteinsmentioning
confidence: 99%
“…[265] Multivalent cations such as Y 3 + are able to form cation bridges between negatively charged areas on protein molecules, [19] thus introducing an effective short-ranged attraction between the proteins. Interestingly, under appropriate experimental conditions, LLPS occurs [257,266] with a lower critical solution temperature (LCST-LLPS), i. e., representing an entropy-driven transition, [187] most likely related to the release of hydration water around the multivalent cation. Given that entropic considerations usually favour phase separation for globular, folded proteins upon a temperature decrease, [295] this behaviour is rather unusual and most likely linked to release of hydration water.…”
Section: 3)mentioning
confidence: 99%